Quiet luxury consumer dynamics: the significance of sustainability in quiet luxury consumers purchase decisions - Flöring, Debora Christine (2024)
Quiet luxury is defined as the consumption of subtly marked products recognized by consumers with the cultural capital to decode these signals (Berger and Ward 2010). This consumer segment has experienced notable growth, accelerated by the emerging quiet luxury trend. However, there is limited research on whether sustainability is a primary purchase driver for quiet luxury consumers. Qualitative research found that sustainability is not a primary consideration in quiet luxury purchases. Nonetheless, consumers expect luxury brands to engage in ESG practices and adhere to ethical standards. Therefore, research recommends brands embed ESG initiatives in their DNA and communicate them transparently.